Adapted Bacteriophages for Treating Urinary Tract Infections - Ujmajuridze, Aleksandre; Chanishvili, Nina; Goderdzishvili, Marina; Leitner, Lorenz; Mehnert, Ulrich; Chkhotua, Archil; Kessler, Thomas M.; Sybesma, Wilbert (Frontiers in Microbiology, 2018)
Urinary tract infections (UTIs) are among the most widespread microbial diseases and their economic impact on the society is substantial. The continuing increase of antibiotic resistance worldwide is worrying. As a consequence, well-tolerated, highly effective therapeutic alternatives are without delay needed. Although it has been demonstrated that bacteriophage therapy may be effective and safe for treating UTIs, the number of studied patients is low and there is a lack of randomized controlled trials (RCTs). The present study has been designed as a two-phase prospective investigation: 1) bacteriophage adaptation, 2) treatment with the commercially available but adapted Pyo bacteriophage. The aim was to evaluate feasibility, tolerability, safety and clinical / microbiological outcomes in a case series as a pilot for a double-blind RCT. In the first phase, patients planned for transurethral resection of the prostate were screened (n=130) for UTIs and enrolled (n=118) in the study when the titer of predefined uropathogens (Staphylococcus aureus, E. coli, Streptococcus spp., Pseudomonas aeruginosa, Proteus mirabilis) in the urine culture was ≥104 colony forming units/mL. In vitro analysis showed a sensitivity for uropathogenic bacteria to Pyo bacteriophage of 41% (48/118) and adaptation cycles of Pyo bacteriophage enhanced its sensitivity to 75% (88/118). In the second phase, nine patients were treated with adapted Pyo bacteriophage and bacteria titer decreased (between 1 and 5 log) in six of the nine patients (67%). No bacteriophage-associated adverse events have been detected. The findings of our prospective two-phase study suggest that adapted bacteriophage therapy might be effective and safe for treating UTIs. Thus, well-designed RCTs are highly warranted to further define the role of this potentially revolutionizing treatment option.